Neoplasia mammary in cats and dogs in the city of Aracaju-Brazil - Nascimento, Júlio César; da Silva Leal, Gabriela; dos Santos, Teresinha Maria (Pubvet, 2017)
The objective of this research was to observe the incidence of breast tumor in companion animals treated at the Dr. Vicente Borelli Veterinary Hospital in the city of Aracaju, SE during the year 2015. Data from 38 patients affected by neoplasias were evaluated. The evaluation criteria used included race, age and weight, ordering the values found and submitting the frequency analysis. After the study, it was found that there was a greater involvement of animals between zero and ten kilograms (58.1%), age from six years (80.6%) and were mainly Without Definite Race ( 35.5%), followed by poodle (32.3%), Pit Bull (12.9%), Pinscher and Dachshund (6.5%), German Shepherd and Coocker (3.2%). In the felines the high prevalence occurred with weight between zero and four kilos (57.1%), age from six years (85.7%) being Siamese the most affected race (71.4%), followed by Hair Brazilian Short (28.6%). It is concluded that senile animals independent of the species are more predisposed to acquire the disease. But dogs are affected to a greater extent. Therefore, it is essential to have a closer monitoring of older dogs and cats by the Veterinarian. Are needed other studies and research in the area of Veterinary Oncology to better understand the relevant aspects of mammary neoplasia.
Keywords: Casuistry; neoplasia; small animals